Analysis of Emission Reduction Measures and Simulation of PM2.5 Concentrations in the Main Cotton Production Areas of Xinjiang in 2025 - Chunsheng Fang; Zhuoqiong Li; Xiao Liu; Weihao Shi; Dali Wang; Ju Wang (Atmosphere, 2024)
Cotton production in Xinjiang is increasing year by year, and the improved crop yields have had an impact on the environment. This study investigated the changes in six significant pollutants (PM2.5, PM10, SO2, NO2, O3, and CO) from 2017 to 2022 in Xinjiang. We compiled a biomass burning emission inventory to make the MEIC emission inventory more complete. The Weather Research and Forecasting Community Multiscale Air Quality (WRF–CMAQ) model was employed to simulate air quality in different reduction scenarios in 2025, and it explored ways to alleviate air pollution in the main cotton areas of Xinjiang. The result shows that the main pollutant in Xinjiang is particulate matter (PM particles with aerodynamic diameters less than 2.5 µm and 10 µm), and the concentration of particulate matter decreased from the northern mountains toward the south. The concentrations of O3 (ozone) were highest in summer, while the concentrations of other pollutants were high in autumn and winter. If the pollution is not strictly controlled in terms of emission reduction, it is impossible to achieve the target of a 35 μg/m3 PM2.5 concentration in the planting area. In the scenario of enhanced emission reduction measures and the scenario of higher intensity emission reduction measures, there was a failure to reach the target, despite the reduction in the PM2.5 concentration. In the best emission reduction scenario, PM2.5 in Xinjiang is expected to drop to 22.5 μg/m3 in November and 34 μg/m3 in March, respectively. Therefore, in the optimal emission reduction scenario, the target of 35 μg/m3 will be reached. This study emphasized the importance of future air pollution mitigation and identified a feasible pathway to achieve the target of 35 μg/m3 PM2.5 concentration by 2025. The research findings provide useful insights for the local government which can be used to develop strategies aimed at mitigating substantial pollution emissions.